IoT Based Health Monitoring System for Elderly Patient - Hasshim, Mohamad Hariz; Nordin, Shahilah; Hamzah, Shipun Anuar; Ramli, Khairun Nidzam; Adon, Mohamad Nazib; Zainal, Mohamad Shamian; Mustapa, Mohammad Sukri; Nik Abd Malik, Nik Noordini (Journal of Electronic Voltage and Application, 2020)
The joy of the loved ones is among the key factors to our happier lives. For the best life, people require extra attention from health monitoring point in order to stay healthy and safe. Therefore, a practical innovation product to monitor patient health such as the elderly monitoring system are developed and proposed in this article. The product is based on IoT where it can monitor the body’s temperature, pulse rate and respiratory rate of the patient on a long distance using smartphones. The proposed system uses nodeMCU as a microcontroller, three sensors units and ThingSpeak as application platform. A smart lifestyle typically among the elderly can be developed using innovative products like this in the future. It can help doctors and guardians to monitor elderly patients from long-haul distance.